2016
DOI: 10.1111/jpy.12433
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salinity on the cellular permeability and cytotoxicity of Heterosigma akashiwo

Abstract: A laboratory study using the fish-killing raphidophyte Heterosigma akashiwo was conducted to examine its capability to grow at salinities below oceanic, and to test the perceived relationship between reduced salinities and increased cytotoxicity. A nonaxenic strain of H. akashiwo isolated from the U.S. Pacific Northwest was exposed to a combination of three salinity (32, 20, and 10) and five temperature (14.7°C, 18.4°C, 21.4°C, 24.4°C and 27.8°C) conditions. Our results demonstrate that cell permeability and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
(119 reference statements)
2
10
0
Order By: Relevance
“…Another possible explanation for this is that single species blooms may escape the important mortality-inducing factors such as allelopathy (Vardi et al, 2002;Poulin et al, 2018). Increased production of allelopathic chemicals might be induced by the presence of competing species (Ikeda et al, 2016). Also, the polyunsaturated aldehydes released by diverse phytoplankton, especially diatoms (Wichard et al, 2005), have been shown, among other effects, to cause membrane permeability in other phytoplankton species (Casotti et al, 2005;Ribalet et al, 2007).…”
Section: Variation In Phytoplankton Viabilitymentioning
confidence: 99%
“…Another possible explanation for this is that single species blooms may escape the important mortality-inducing factors such as allelopathy (Vardi et al, 2002;Poulin et al, 2018). Increased production of allelopathic chemicals might be induced by the presence of competing species (Ikeda et al, 2016). Also, the polyunsaturated aldehydes released by diverse phytoplankton, especially diatoms (Wichard et al, 2005), have been shown, among other effects, to cause membrane permeability in other phytoplankton species (Casotti et al, 2005;Ribalet et al, 2007).…”
Section: Variation In Phytoplankton Viabilitymentioning
confidence: 99%
“…The ichthyotoxic raphidophyte Heterosigma akashiwo , a golden–brown unicellular microalga causing harmful algal blooms, has been frequently observed in coastal waters around the world over the past few decades [ 1 , 2 , 3 , 4 ]. H. akashiwo blooms are sporadic and are responsible for the fatality of cultured and wild fish in different parts of the world such as North America (including Canada and the United States) [ 4 , 5 , 6 , 7 , 8 ], Mexico [ 9 ], Japan [ 10 , 11 ], Chile [ 12 ], China [ 13 ], New Zealand [ 14 ], Europe (such as Spain) [ 15 ], and Norway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different environmental factors affect toxin production depending on the HABs taxon [ 11 , 30 , 31 , 32 , 33 , 34 ]. A direct correlation was detected between environmental factors such as light, temperature and salinity and the growth and toxicity of H. akashiwo in different geographical areas [ 3 , 10 , 11 , 23 , 24 ]. For the Japanese strain the highest toxicity was observed at a light intensity of 200 μmol photons m −2 s −1 , and a temperature lower than 25 °C [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using mice as a bioassay models has been debatable since they were first used, due to unreliability and the associated ethical issues [43,44]. Various cell lines obtained from different animals including a mouse [45], a rat [34], fish gill cells [46][47][48][49], or human tissues such as human hepatoma cell line (HepG2) [50], or human colon carcinoma cell line (Caco-2) [51], are recommended and have been used to measure different types of toxins produced by algal bloom species. Using whole organisms or their cell lines as a bioassay model for ichthyotoxicity measurement obligates prolonged exposure or follow-up periods, and therefore increases the errors in evaluation.…”
Section: Introductionmentioning
confidence: 99%